2018
DOI: 10.3389/fmicb.2018.02769
|View full text |Cite
|
Sign up to set email alerts
|

Fructo-Oligosaccharide Alleviates Soybean-Induced Anaphylaxis in Piglets by Modulating Gut Microbes

Abstract: Soybean-induced anaphylaxis poses a severe threat to the health of humans and animals. Some commensal bacteria, such as Lactobacillus and Bifidobacteria, can prevent and treat allergic diseases. Prebiotic oligosaccharides, a food/diet additive, can enhance health and performance via modulating gut microbes and immune responses. The purpose of this study was to examine whether fructo-oligosaccharides (FOS) could alleviate soybean-induced anaphylaxis by modulating gut microbes. Piglets (21 days of age) were sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 63 publications
2
24
0
Order By: Relevance
“…During the sensitization stage, the piglets in the sensitized group were fed with an allergic diet using soybean, and the control diet was given on all the other days. The ingredients of the swine diets were described in our previous study ( 7 ). Briefly, the control diet contained 11.13% casein, 65.70% corn, 4.50% bran, 7.19% whey powder, 2.0% fish meal, 1.02% digested tankage, and 8.46% supplement (mineral, vitamins, amino acids, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the sensitization stage, the piglets in the sensitized group were fed with an allergic diet using soybean, and the control diet was given on all the other days. The ingredients of the swine diets were described in our previous study ( 7 ). Briefly, the control diet contained 11.13% casein, 65.70% corn, 4.50% bran, 7.19% whey powder, 2.0% fish meal, 1.02% digested tankage, and 8.46% supplement (mineral, vitamins, amino acids, etc.…”
Section: Methodsmentioning
confidence: 99%
“…At least 21 soybean allergens have been identified in humans ( 3 ), causing allergic symptoms including skin rash, gastrointestinal problems, rhinitis, asthma, hypotension, and anaphylaxis. Furthermore, soybean protein induces an allergic response in some animal species, such as swine ( 4 7 ), bovine ( 8 , 9 ), rats ( 10 ), and dogs ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…(2018) FOS Dogs 1.5 g/kg 4 wk ↑ Bifidobacteria, acetic-to-propionic acid ratio ↓ pH in faces, acetic + n-butyric acid-to-propionic acid ratio Pinna et al. (2018) FOS Weaned piglets 0.6% 7 d ↑ Bifidobacteria , Lactobacillus in jejunum ↑ IFN-γ ↓ Proteobacteria in jejunum and ileum ↓ IL-4, IL-10 Chang et al. (2018) scFOS 18-wk-old obese male C57BL/6J mice 10% 4 wk ↑ Cecal and colonic crypt depth, transmural resistance ↑ Actinobacteria, Verrucomirobia Liu et al.…”
Section: Prebiotics and Intestinal Health Of Monogastric Animalsmentioning
confidence: 99%
“…FOS fermentation results in the stimulation of the activities of probiotic bacteria, such as Lactobacillus and Bifidobacterium, which are part of the intestinal commensal microbiota (Salminen et al, 1998;Macfarlane and Cummings, 1999;Boguslawska-Tryk et al, 2012). Consequently, cecal SCFA and lactate content increase, thereby inhibiting the activity of harmful bacteria such as Escherichia coli or Salmonella species in the gut (Hidaka et al, 1986;Choi et al, 1994;Bunce et al, 1995;Fukata, 1999;Xu et al, 2002). Xu et al (2002) confirmed the same when 4 and 6 g kg −1 FOS (type is described in Sect.…”
Section: Gut Microbiota Compositionmentioning
confidence: 86%